Gambaran Dukungan Sosial Orang Tua dalam Perencanaan Karier Anak Disabilitas Rungu-Wicara di SLB Asuhan Kasih Kota Kupang - Christin Aljelia Bulla; Yeni Damayanti; Marleny P. Panis (Pusat riset dan Inovasi Nasional, 2025)
This study discusses the importance of parental social support in career planning for deaf children, who have communication limitations and need special assistance in developing their potential. This study was conducted because parents often experience anxiety about the future of their deaf-speech disabled children, especially in determining appropriate career paths. This study aims to describe forms of parental social support in the process of children's career planning. This study used a descriptive qualitative method with purposive sampling and semi-structured interviews with four parents of deaf students at SLB Asuhan Kasih Kupang. The results of the thematic analysis show that emotional, informative, and modeling support are the main forms of support provided by parents. Other supporting factors include the school environment, the exploration of children's interests, and parental expectations. These findings emphasize the importance of active parental involvement in optimally preparing children with hearing disabilities for their careers.